Evaluation of BBIBP-CorV Sinopharm COVID-19 vaccine effectiveness in Sri Lanka: a test-negative case control study - Dileepa Senajith Ediriweera; Shamila Thivanshi De Silva; Wathsala Wimalasena; Manjula Kariyawasam; Gihan Kosinna; Gayan Bogoda; Sumudu Senaratne; Kanchana Rathnayake; Inosha Weerarathna; Ranjan Premaratna; Prasanna Gunasena (BMJ Open, 2024)
Objectives There is limited research on real-world effectiveness of BBIBP-CorV Sinopharm COVID-19 vaccine. This study evaluated real-world effectiveness of Sinopharm vaccine in Sri Lanka by assessing absolute vaccine efficacy.Design and setting A retrospective test-negative case-control study was conducted at ten large government hospitals across the country.Participants Consecutive adults aged ≥18 years attending outpatient departments who tested reverse-transcription-PCR positive for SARS-CoV-2 during the study period were recruited.Main outcome measures An interviewer-administered questionnaire was administered, and outcome of COVID-19 infection was assessed in cases.Results Of 1829 recruited, 914 (49.9%) were male, and mean age was 45.2 (SD 15.3) years; 1634 (89.3%) were vaccinated with two doses of BBIBP-CorV Sinopharm vaccine, while 195 (10.1%) were vaccine-naïve. Compared with the vaccinated, unvaccinated persons were older but otherwise similar in their demographic and medical profiles. Unvaccinated were more likely to have fever, shortness of breath and vomiting as symptoms and were more likely to seek treatment. Significantly more vaccinated individuals received treatment at home. After admission, the unvaccinated were more likely to receive oxygen. Significantly more unvaccinated persons died of COVID-19 compared with the vaccinated. Sinopharm vaccine was 78.2% (94% CI 69.0% to 85.0%) effective at preventing COVID-19 infection, 88.7% (81.6%–93.2%) effective at preventing severe infection and 85.6% (69.6%–93.6%) effective at preventing death.Conclusions BBIBP-CorV Sinopharm vaccine is effective at mitigating severity of illness and reducing the likelihood of hospitalisation, severe illness and death, in those who received primary vaccination, compared with the unvaccinated.